SPE Eastern Regional Meeting 2005
DOI: 10.2118/98012-ms
|View full text |Cite
|
Sign up to set email alerts
|

Reservoir Characterization Using Intelligent Seismic Inversion

Abstract: RESERVOIR CHARACTERIZATION USING INTELLIGENT SEISMIC INVERSION F. Emre ArtunIntegrating different types of data having different scales is the major challenge in reservoir characterization studies. Seismic data is among those different types of data, which is usually used by geoscientists for structural mapping of the subsurface and making interpretations of the reservoir's facies distribution. Yet, it has been a common aim of geoscientists to incorporate seismic data in high-resolution reservoir description t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The benefits of these algorithms include enhanced resolution and accuracy, particularly in cases where distinct layered structures exist. However, challenges, such as selecting appropriate regularization parameters, correct initial model and addressing non-uniqueness in the sparse layer reflectivity inversion process, need careful consideration, making this method suitable for cases where a simple interpretable geological model is desired [26][27][28][29].…”
Section: Sparse Layer Reflectivity Inversionmentioning
confidence: 99%
“…The benefits of these algorithms include enhanced resolution and accuracy, particularly in cases where distinct layered structures exist. However, challenges, such as selecting appropriate regularization parameters, correct initial model and addressing non-uniqueness in the sparse layer reflectivity inversion process, need careful consideration, making this method suitable for cases where a simple interpretable geological model is desired [26][27][28][29].…”
Section: Sparse Layer Reflectivity Inversionmentioning
confidence: 99%
“…The algorithmic form of this network can be used for any regression problem where there are no assumptions for linear judgment. This network does not have the parameters of the error propagation network but instead does not have the error smoothing factor; instead, the smoothing factor is obtained by considering the mean squared error (Artun et al, 2005), as shown in Figure 2. The structure of this network is similar to the general structure of the radial network; there is only a slight difference in the second layer.…”
Section: General Regression Neural Networkmentioning
confidence: 99%
“…In this study, worldwide experimental data from open literature were used to construct an improved, integrated intelligent model for estimating oil‐CO 2 MMP . Intelligent systems have had a great appeal for researchers in recent years . However, the quest for higher accuracy causes the development of integrated approaches and committee machines .…”
Section: Introductionmentioning
confidence: 99%